2017
DOI: 10.33898/rdp.v28i106.143
|View full text |Cite
|
Sign up to set email alerts
|

Una propuesta para abordar la doble ceguera: la Terapia Familiar Crítica sensible al Género.

Abstract: En este texto reflexionamos sobre los sesgos de género en la terapia familiar, así como las implicaciones que tienen en el proceso de salud-enfermedad, diagnóstico y tratamiento de hombres y mujeres, y evidenciamos la doble ceguera respecto al género imperante en la disciplina: no sólo no sabemos sino que no sabemos que no sabemos. A continuación exponemos argumentos que abogan por el desarrollo de una terapia familiar crítica sensible al género desde la formación de las y los psicoterapeutas, lo cual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The implications of being accurate for the quality of couple relationships highlight the importance of using interventions that aim to explore metaperceptions about partners and the relationship, taking into account gender differences and the impact of expectations derived from gender socialization in personal well‐being and relationship satisfaction. Circular questions considering gender perspective (Macias‐Esparza & Laso Ortiz, 2017) and the use of qualitative grids (Procter, 2014) may help to achieve this goal as they contribute to bringing into open discussion the couples’ interpersonal perception process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of being accurate for the quality of couple relationships highlight the importance of using interventions that aim to explore metaperceptions about partners and the relationship, taking into account gender differences and the impact of expectations derived from gender socialization in personal well‐being and relationship satisfaction. Circular questions considering gender perspective (Macias‐Esparza & Laso Ortiz, 2017) and the use of qualitative grids (Procter, 2014) may help to achieve this goal as they contribute to bringing into open discussion the couples’ interpersonal perception process.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its association with relationship quality, some studies report gender differences with regard to actor and partner effects and the attributes assessed (e.g., Cohen et al, 2012), whereas others have found no such differences (Sened et al, 2017). However, from a large body of literature (e.g., Macias‐Esparza & Laso Ortiz, 2017), we know that gender socialization might play an important role in the attitudes and perceptions of opposite‐sex couples, but to date, we could not find studies detailing and testing this influence.…”
Section: Introductionmentioning
confidence: 99%
“…iamente las posibilidades de desarrollo personal de unos y otras, al prescribir un determinado camino para hombres y otro para mujeres. Además, si no lo abordamos explícitamente, la condición de terapeutas no nos exime de este proceso de socialización que compartimos con las personas que atendemos en terapia y, como ellas, permanecemos ciegas al impacto que tiene (Macías y Laso, 2017). Tal y como argumenta Harry Procter (2016Procter ( , 2021, reconocer la importancia de estos factores culturales no significa renunciar a la idiosincrasia de las personas que atendemos.…”
Section: La Desigualdad En Las Sociedades Formalmente Igualitariasunclassified
“…Another lesson from the global crisis is to recognize that a large part of the symptomatology manifested during the pandemic is linked to the patriarchy (Medina, 2022a). Depression, anxiety, alcohol, and drug abuse, and femicide are the symptomatic expression of a lifestyle governed by patriarchal culture, which is represented in patterns of control, manipulation, exclusion, and abuse of those members who do not comply with the imaginary of the traditional heterosexual nuclear family (Macías- Esparza & Laso, 2017;Walters et al, 1988).…”
Section: Patriarchy As a Generator Of Personal Malaisementioning
confidence: 99%